Ethnobotanical, Phytochemical, Toxicological, and Pharmacological Properties of Ziziphus lotus (L.) Lam.: A Comprehensive Review - Noureddine Bencheikh; Fatima Zahrae Radi; Jamila Fakchich; Amine Elbouzidi; Sabir Ouahhoud; Mohammed Ouasti; Mohamed Bouhrim; Imane Ouasti; Christophe Hano; Mostafa Elachouri (Pharmaceuticals, 2023)
Ziziphus lotus (L.) Lam. (Rhamnaceae) is a plant species found across the Mediterranean area. This comprehensive overview aims to summarize the botanical description and ethnobotanical uses of Z. lotus and its phytochemical compounds derived with recent updates on its pharmacological and toxicological properties. The data were collected from electronic databases including the Web of Science, PubMed, ScienceDirect, Scopus, SpringerLink, and Google Scholars. It can be seen from the literature that Z. lotus is traditionally used to treat and prevent several diseases including diabetes, digestive problems, urinary tract problems, infectious diseases, cardiovascular disorders, neurological diseases, and dermal problems. The extracts of Z. lotus demonstrated several pharmacological properties in vitro and in vivo such as antidiabetic, anticancer, anti-oxidant, antimicrobials, anti-inflammatory, immunomodulatory, analgesic, anti-proliferative, anti-spasmodic, hepatoprotective, and nephroprotective effects. The phytochemical characterization of Z. lotus extracts revealed the presence of over 181 bioactive compounds including terpenoids, polyphenols, flavonoids, alkaloids, and fatty acids. Toxicity studies on Z. lotus showed that extracts from this plant are safe and free from toxicity. Thus, further research is needed to establish a possible relationship between traditional uses, plant chemistry, and pharmacological properties. Furthermore, Z. lotus is quite promising as a medicinal agent, so further clinical trials should be conducted to prove its efficacy.